Ecological Niche as the Factor Determining Cryoresistance in Fish Spermatozoa - Kopeika, Evgeniy F. (Problems of Cryobiology and Cryomedicine, 2014)
In this research we have compared the spermatozoa cryoresistance of fish species from different ecological niches and explained the nature of differences based on our own results and published data. Differences in spermatozoa cryoresistance of fish species, spawning in fresh water at 0...10°C (6 species of salmonids), 18...25°C (5 species of carp) and in marine water at 16...25°C (mullet-golden mullet) were established using cryopreservation and visual assessment methods for sperm motility. Quantitative and qualitative differences in motility of frozen-thawed fish sperm from different ecological niches were established as stipulated by different strength of molecule-to-molecule bonds of membrane lipids and the ratio between components, determining the formation of hydrophilic pores at lipid phase transitions. Probl Cryobiol Cryomed 2014; 24(4):302-311.